Head Teacher’s Leadership Styles and the Quality of Teacher Support Supervision - Tibagwa, Kate Norah; Onen, David; Oonyu, Joseph (International Journal of Education and Research, 2016)
This paper examines the relationship between head teacher’s leadership styles and the quality of support supervision offered to teachers in primary schools in Mid-western Uganda. The study was driven by the need to establish the largely and widely held belief that school heads make a difference on instructional effectiveness of teachers through effective leadership and the kind of support supervision they provide teachers in their schools. The researchers employed a correlational cross-sectional survey design in which both quantitative and qualitative data were collected from a study sample of 320 teachers and 20 educational administrators using questionnaire survey and interview methods. The data were analysed with the use of descriptive and inferential statistical techniques as well as content analysis method. Study results revealed that both people-oriented, and task-oriented styles of leadership have statistically significant correlation (r = .566, p = .000) and (r = .536, p = .000) respectively, with the quality of teacher support supervision. But laissez-faire style of leadership has a statistically weak correlation (r = .117, p = .057) with the quality of teacher support supervision. The researchers thus concluded that the type of leadership styles that school heads use have a bearing on the quality of teacher support supervision. Consequently, it was recommended that school heads should make use of appropriate leadership styles to suit situations, needs and developmental aspirations of teachers as well as the needs of the primary schools they serve.
Keywords: Leadership; leadership styles; Teachers; Support supervision; Primary schools